Quo Vadis Technology-Based Companies to Issue MVS When Conducting an IPO on the IDX - Keumala, Dinda; Sabirin, Ahmad; Balqies, Izzah; Pahlevi, Ahmad Gozzy (Audito Comparative Law Journal (ACLJ), 2024)
This paper aims to examine whether technology-based companies issue multiple voting shares when conducting an initial public offering on the stock exchange is needed in Indonesia to be an urgency in Indonesia. The application of multi-voting shares must follow the stipulated provisions, starting from the share lock-up period to the validity period of the multi-voting shares. This article used normative legal research methods. The research findings show that shares with multiple voting rights give a lot of votes to old shareholders with a determination before the initial public offering and determined in the articles of association of the company. New shareholders, despite owning the majority of shares, only have 1 (one) vote per share or as in Law Number 40 of 2007 concerning Limited Liability Companies known as “one share one vote”. This optional policy implies that the shareholders, although the majority, do not control the company. This means that ordinary shareholders, although the majority, can only enjoy profits through capital gains and dividend distribution. However, if the issuer suffers a loss, the ordinary shareholders, who are the majority shareholders, will suffer the biggest loss.